SOSIALISASI BAHAYA NARKOBA DAN MINUMAN KERAS SERTADAMPAK HUKUM BAGI PENGGUNANYA - Sidiq Tono (UII, 2014)
Indonesia as a country with an enormous population became a target for drugdealers and liquor. Currently drugs and alcohol are not only available in urban areas butalso have entered into the countryside. The target of drug dealers and liquor wereyoungmen. Dusun Pencil Munggung village, Klaten Karangdowo is one of the villagesthat have quite a lot of young cadres. The village youth if not given knowledge about thedangers of drugs and alcohol it will potentially be a user or can be dealer. Seeing thepotential dangers of drugs and alcohol is so great it threatens to do the preventionprocess by conducting socialization program dangers of drugs and alcohol as well as thelegal impact for users in the hamlet Pencil. After the socialization of the youth programto understand the dangers of using drugs and alcohol so that so the youth would not beinterested in taking drugs or liquor.